Post a New Question

amy

posted by on .

how do i solve this

2 ln(x-3)= ln(x+5) + ln4

  • amy - ,

    Use the laws of logarithm:
    ln a + ln b = ln ab
    2ln a = ln a²

    2 ln(x-3)= ln(x+5) + ln4
    =>
    ln(x-3)² = ln 4(x+5)
    Raise to power of e:
    (x-3)² = 4(x+5)
    Simplify and factor to get:
    (x-11)*(x+1)=0
    Can you take it from here?

  • amy - ,

    yes thank you much! :)

  • amy :) - ,

    :)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question